Old sins cast long shadows: The Long-term impact of the resettlement of the Sudetenland on residential migration - Martin Guzi; Peter Huber; Stepan Mikula (Masaryk University, Faculty of Economics and Administration, 2019)
We analyze the long-term impact of the resettlement of the Sudetenland after World War~II on residential migration. This event involved expulsion of ethnic Germans and almost complete depopulation of an area of a country and its rapid resettlement by 2 million Czech inhabitants. Results based on nearest neighbor matching and regression discontinuity design show a higher population churn in resettled areas that continues today. The populations in resettled areas and in the remainder of the country share similar values and do not differ statistically in terms of their propensity to give donations, attend social events, and participate in voluntary work. However, we observe that resettled settlements have fewer local club memberships, lower turnout in municipal elections, and less frequently organized social events. This finding indicates substantially lower local social capital in the resettled settlements that is likely to have caused higher residential migration. This explanation is consistent with theoretical models of the impact of social capital on migration decisions.
Keywords: N44; Z10; R23; J15; 330; Migration; Social Capital; Sudetenland